Adjuvant Proton Beam Radiation Therapy for Sinonasal Mucosal Melanoma - Jamie S. K. Takayesu; Upendra Parvathaneni; George E. Laramore; Neil Panjwani; Jennifer Sillings; Neal D. Futran; Ian M. Humphreys; Aria Jafari; Waleed M. Abuzeid; Brittany Barber; Emily Marchiano; Sylvia M. Lee; et al. (Cancer Reports)
ABSTRACT Background Head and neck mucosal melanoma (HNMM) is rare and carries a poor prognosis with high rates of disease progression. There is little data regarding the use of adjuvant proton radiation therapy in the management of sinonasal HNMM. Aims We performed a retrospective review of patients with nonmetastatic sinonasal HNMM treated with adjuvant proton radiation from 2012 to 2022 at a single academic institution. Kaplan–Meier estimates were used for survival analyses. Methods and Results Eight patients with sinonasal HNMM were treated with surgery and adjuvant proton radiation, and six received systemic therapy. Median follow‐up was 15 months (range: 3–68 months). Only one local failure was observed, and two patients developed distant metastases. Kaplan–Meier 1‐year results were as follows: local control 88%, distant metastasis‐free survival 75%, and overall survival 88%. No Grade 3 or higher late toxicities were observed. Conclusion Surgical resection and adjuvant proton radiation provided early favorable local control and toxicity profiles in our cohort of patients with sinonasal HNMM. Further multi‐institutional work is needed to study this rare malignancy.